2017
DOI: 10.5455/ijlr.20170312053224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotic, Prebiotic and Synbiotic on Hematological Parameters of Crossbred Calves

Abstract: The present study was conducted to evaluate the impact of probiotic, prebiotic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…The increase in hemoglobin level was also confirmed by Dar et al [22]. We assessed the influence of probiotics, prebiotics, and synbiotics on the hematological parameters of the calves and found that from the 30 th day of the experiment until the end of the research, the calves' hemoglobin levels were increasing.…”
Section: Discussionsupporting
confidence: 75%
“…The increase in hemoglobin level was also confirmed by Dar et al [22]. We assessed the influence of probiotics, prebiotics, and synbiotics on the hematological parameters of the calves and found that from the 30 th day of the experiment until the end of the research, the calves' hemoglobin levels were increasing.…”
Section: Discussionsupporting
confidence: 75%
“…The present results are in accordance with the findings of Roodposhti and Dabiri (2012) who reported significantly higher (P<0.05) body weights in Holstein female calves supplemented with synbiotic compared to the control calves. Dar et al, (2017) and Abdel-Raheem et al, (2012) also reported significantly (P<0.05) higher body weight gains in calves supplemented with probiotic and synbiotic over control.…”
Section: Mean Body Weightmentioning
confidence: 87%
“…Synbiotics are a combination of prebiotics and probiotics that benefits the host by selectively stimulating the growth or by activating the metabolism of health-promoting bacteria, and thus improving host welfare. Dietary Supplementation of synbiotics increased average daily gain and reduced fecal shedding of E.coli in calves (Roodposhti and Dabiri, 2012) and improved body weight and was affordable (Dar et al, 2017). Since there is paucity of information the present research is proposed to study the effect of synbiotic supplementation in growth performance of buffalo calves.…”
Section: Introductionmentioning
confidence: 99%
“…Statistically there was no significant difference in Total Erythrocyte count (10 6 /μl) of different group at different time interval. Dar et al, (2017) reported that the TEC not affected by the feeding of Probiotic, Prebiotic and Synbiotic in cross bred calves.…”
Section: Total Erythrocyte Count (10 6 /μL)mentioning
confidence: 97%